Sistem Informasi Pelaporan Lapinhar, Lapinsus, dan Lapbangsit di Kejaksaan Negeri Penajam Paser Utara Berbasis Web - Meidianto, M. Guntur (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This study aims to analyse the Web-Based Lapinhar, Lapinsus, and Lapbangsit Reporting Information System at the Penajam Paser Utara District Attorney's Office. This information system is a tool for presenting information in such a way that it is useful for the recipient through the services available in this system. The research site was conducted at the North Panajam Paser State Attorney's Office. Data collection methods are observation, interviews. Secondary data of this research is obtained from books, journals, and previous research. The result of this research is that a web-based information system has been successfully developed which aims to simplify the process of reporting and managing data in three important fields in the North Penajam Paser State Attorney's Office, namely Lapinhar (General Criminal Report), Lapinsus (Special Criminal Report), and Lapbangsit (System Build Report). Through careful analysis and design, this information system provides an effective solution in overcoming the obstacles that existed in the previous manual system.